2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of LTMS-S: A wearable system for vital signs monitoring

Abstract: LTMS-S is a new wearable system for the monitoring of several physiological signals--including a two-lead electrocardiogram (ECG)--and parameters, such as the heart rate, the breathing rate, the peripheral oxygen saturation (SpO2), the core body temperature (CBT), and the physical activity. All signals are measured using only three sensors embedded within a vest. The sensors are standalone with their own rechargeable battery, memory, wireless communication and with an autonomy exceeding 24 hours. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…SpO2 (arterial oxygen saturation) is normally measured at the fingertip, but recent experiments [10] suggest that it can be also captured from the chest, at least under certain conditions. Skin temperature is easy to monitor but has limited physiological meaning.…”
Section: Cardiorespiratory Signals Of Interestmentioning
confidence: 99%
See 3 more Smart Citations
“…SpO2 (arterial oxygen saturation) is normally measured at the fingertip, but recent experiments [10] suggest that it can be also captured from the chest, at least under certain conditions. Skin temperature is easy to monitor but has limited physiological meaning.…”
Section: Cardiorespiratory Signals Of Interestmentioning
confidence: 99%
“…Skin temperature is easy to monitor but has limited physiological meaning. CBT (core body temperature) is more difficult to obtain in an unobtrusive way, but some developments show that it might be possible to indirectly sense it from the chest surface [10].…”
Section: Cardiorespiratory Signals Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, we capture physiological signals through exploitation of a newly developed wearable technology developed by the Swiss company CSEM SA (Chételat et al 2015) shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%